Reconstructing Indonesia's Bipartite Labor Dispute Resolution through Customary Bedamai: A Legal Pluralism Perspective - Wahyu Utami; Yogabakti Adipradana Setiawan (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The formal bipartite mechanism in Indonesia's labor dispute resolution, governed by Law No. 2 of 2004, is characterized by rigidity, adversarial dynamics, and a frequent lack of good faith, creating a systemic bottleneck in industrial relations that undermines both worker welfare and enterprise productivity. Integrating the customary Bedamai approach, rooted in Banjar adat traditions, offers a restorative, consensus-driven solution to this persistent controversy. Through the analytical lens of legal pluralism, a critical gap exists between the positivist state labor law framework and the sociological need for harmonious, culturally resonant dispute resolution mechanisms that reflect Indonesia's diverse legal traditions. This study aims to reconstruct the formal bipartite mechanism by integrating the bedamai customary approach to achieve more effective and harmonious dispute settlements that honor both statutory requirements and indigenous values. The research employs a purely normative legal method utilizing statutory, conceptual, and cultural approaches, analyzing primary and secondary legal materials without empirical fieldwork, thereby focusing on doctrinal analysis and legal reconstruction. The findings reveal that bedamai fundamentally shifts the paradigm from adversarial rights-claiming to restorative relationship-building, emphasizing communal harmony over individual victory. A reconstructed "Bipartite-bedamai Integration Model" is formulated, embedding customary consensus-building and community facilitation into the statutory negotiation phase while maintaining legal enforceability. The study concludes that legal pluralism must move beyond sociological observation toward normative integration, recommending specific amendments to Law No. 2 of 2004 to formally recognize customary mechanisms as a valid, parallel, or preliminary bipartite process